2017
DOI: 10.5603/gp.a2017.0095
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum neuregulin 4 levels in women with polycystic ovary syndrome: A case-control study

Abstract: Objectives: Neuregulin 4 (NRG4) is an adipokine that is synthesized in many tissues and has been shown to be associated with the development of obesity and metabolic disorders in animals and humans. The aim of this study is to investigate the relationship between serum NRG4 levels and various metabolic parameters in women with PCOS. Material and methods:This cross-sectional study included 40 women with PCOS and 40 age-and BMI-matched controls without PCOS. NRG4, fasting blood glucose (FBG), insulin, hs-CRP, LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The ERBB4 receptor gene was associated with PCOS on the basis of a GWAS in Caucasian patients (15,31) and replicated by a case-control study in Chinese patients (32). ERBB4 encodes a receptor activated by neuregulin (NRG)4 (33), and serum levels of NRG4 were found to be elevated in patients with PCOS (34,35). In a well-powered GWAS with the application of a subphenotyping algorithm (phenome-wide association study) for PCOS using electronic records, ERBB4 was found to be associated with oligomenorrhea or infertility.…”
Section: Ligands and Receptorsmentioning
confidence: 90%
“…The ERBB4 receptor gene was associated with PCOS on the basis of a GWAS in Caucasian patients (15,31) and replicated by a case-control study in Chinese patients (32). ERBB4 encodes a receptor activated by neuregulin (NRG)4 (33), and serum levels of NRG4 were found to be elevated in patients with PCOS (34,35). In a well-powered GWAS with the application of a subphenotyping algorithm (phenome-wide association study) for PCOS using electronic records, ERBB4 was found to be associated with oligomenorrhea or infertility.…”
Section: Ligands and Receptorsmentioning
confidence: 90%
“…A subsequent study also proposed that hepatic Nrg4 signaling could be an endocrine checkpoint for steatosis-to-steatohepatitis progression by countering stress-induced liver injury, fibrosis and cell death (21). In addition, several studies in human cohorts revealed that Nrg4 levels were increased in patients with prediabetes, newly diagnosed diabetes, gestational diabetes or polycystic ovary syndrome, suggesting Nrg4 concentrations were associated with the development and progression of insulin resistance (22, 23, 24, 25). However, other findings indicate that circulating Nrg4 concentrations may be a protective factor in the development of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Temur et al reported considerably higher serum levels of NRG4 in PCOS patients than in healthy controls [ 137 ]. High sensitivity C-reactive protein (Hs-CRP), low-density lipoproteins (LDL-C), HDL-C and hormones profile (LH; insulin; total testosterone; sex hormone binding globulin, SHBG; dehydroepiandrosterone sulfate, DHEA-SO 4 ), as well as other metabolism-related factors such as fasting blood glucose (FBG), FAI, and HOMA-IR, were also elevated in comparison to healthy individuals.…”
Section: Neuregulin-4mentioning
confidence: 99%
“…Positive correlations between NGR4 level and FBG, insulin, HOMA-IR and hs-CRP were observed in the study group. HOMA-IR, and hs-CRP proved to be independent markers associated with NRG4 [ 137 ]. Hypothetically, the high neuregulin level in PCOS subjects could be interpreted as a result of problems with NRG4 binding to epidermal growth factor receptor (EGFR); however, more research needs to be conducted to confirm this hypothesis [ 137 ].…”
Section: Neuregulin-4mentioning
confidence: 99%
See 1 more Smart Citation